Concentración de abono orgánico foliar (Humus líquido), sobre el rendimiento de forraje del pasto Pennisetum sp. King grass morado en Iquitos, Perú - 2015 - García Matute, Andy Raúl (2016)
This research was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Vaccine Project in the Zungarococha Fundo, entitled “Concentration of Foliar Organic Fertilizer (Liquid Humus), on the forage yield of Pennisetum sp. Purple King grass in Iquitos, Peru - 2015 ”. The evaluations were carried out at the ninth week after sowing with vegetative seed (bushes), in plots of 8 m x 2 m (16 m2) and an experimental area of 1056 m2. With a Random Complete Block Design (DBCA) design, with five treatments and four repetitions, the treatments under study were: T0 (No application), T1 (15% liquid Humus), T2 (30% Liquid Humus), T3 (Humus liquid 45%) and T4 (Humus liquid 60%), the statistical package of SPSS 21 was applied to the field data, giving the following results: It is observed that the best yields were given in the treatment T4 (60% of Liquid humus and 40% water), at plant height with 148.90 cm, coverage with 96.53%, green matter with 4.15 kg / m2 and dry matter with 1.13 kg / m2, and maximum yield of green matter per hectare is 41,475 kilos and the lowest yield of green matter was 19,475 kilos at the 9th week of cutting, it occurred with the concentration of 60% and 15% of liquid humus.